2015
DOI: 10.1007/s11682-015-9479-0
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis of individual differences in the response to mental stress: a magnetoencephalography study

Abstract: Stress is a risk factor for the onset of mental disorders. Although stress response varies across individuals, the mechanism of individual differences remains unclear. Here, we investigated the neural basis of individual differences in response to mental stress using magnetoencephalography (MEG). Twenty healthy male volunteers completed the Temperament and Character Inventory (TCI). The experiment included two types of tasks: a non-stress-inducing task and a stress-inducing task. During these tasks, participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…These bands were chosen as they more often show robust peaks in the spectral density and have previously been shown to be modulated by trait characteristics. For example, Yamano et al (2016) representations of the difference between two conditions. When using contrast maps (instead of investigating the activation of one condition at a time), the other condition works as a baseline, and thus noise is removed, and participants are more comparable to each other.…”
Section: Introductionmentioning
confidence: 99%
“…These bands were chosen as they more often show robust peaks in the spectral density and have previously been shown to be modulated by trait characteristics. For example, Yamano et al (2016) representations of the difference between two conditions. When using contrast maps (instead of investigating the activation of one condition at a time), the other condition works as a baseline, and thus noise is removed, and participants are more comparable to each other.…”
Section: Introductionmentioning
confidence: 99%
“…Personal variation in personality traits was associated with the neural response to mental stress (Yamano et al 2015). The stress reaction is mainly regulated by an axial system consisting of two neuroendocrine systems: the hypothalamic-pituitary-adrenocortical (HPA) axis and sympathetic adrenomedullary system.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown a weaker beta band power in No-Go trials in both non-human primates and healthy and neuropsychiatric human populations 42 , 45 49 . It is possible that increased inhibitory control results in increased beta band activity, while decreased inhibitory control results in reduced beta band activity 50 , 51 . According to these studies, beta power oscillations may be associated with inhibitory control.…”
Section: Introductionmentioning
confidence: 99%